OPERATIONALISING CORPORATE SOCIAL RESPONSIBILITY (CSR) AND THE DEVELOPMENT DEBATE - Salmi Mohd Isa,; Jon Reast, (Asian Academy of Management Journal, 2014)
A considerable amount of attention has been paid to the construct of Corporate Social Responsibility (CSR) and yet research on the precise measurement of CSR has remained limited. Measures have been hampered by a lack of clarity in theoretical frameworks and empirical methods for the CSR construct. Given that the empirical study of CSR measurement is in an undeveloped state, this research describes efforts to justify and prove the relationship between measurement items and the construct. Based on a study among Malaysian stakeholders, this research conceptualises CSR as a formative construct consisting of eight dimensions: process, policy, values, environment, personal, profit, people and politics. The analyses reveal alternative approaches from a conceptual and methodological standpoint that makes clear the danger of misspecifying formative models as reflective, or vice versa. In this regard, it is proposed that the agenda and scope of CSR, as well as the measures used to implement it, are a manifestation of the formative construct that corporations have to operationalise in order to perform CSR better or more efficiently.